2014
DOI: 10.1128/jvi.00104-14
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Differences in Virus Uptake versus Cardiac Function of the Coxsackievirus and Adenovirus Receptor

Abstract: The coxsackievirus and adenovirus receptor (CAR) is a cell contact protein with an important role in virus uptake. Its extracellular immunoglobulin domains mediate the binding to coxsackievirus and adenovirus as well as homophilic and heterophilic interactions between cells. The cytoplasmic tail links CAR to the cytoskeleton and intracellular signaling cascades. In the heart, CAR is crucial for embryonic development, electrophysiology, and coxsackievirus B infection. Noncardiac functions are less well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…5D and E). This confirms the previously described inability of chCAR to mediate CVB3 infection (36) and is consistent with strong evidence that D1 is directly involved in virus binding (7).…”
Section: Fig 2 Loss Of Hcar Glycosylation Has No Influence On Cvb3 Atsupporting
confidence: 78%
See 1 more Smart Citation
“…5D and E). This confirms the previously described inability of chCAR to mediate CVB3 infection (36) and is consistent with strong evidence that D1 is directly involved in virus binding (7).…”
Section: Fig 2 Loss Of Hcar Glycosylation Has No Influence On Cvb3 Atsupporting
confidence: 78%
“…5A). Among these domains, chCAR-D2 shows the greatest sequence homology to hCAR-D2 (45%), although chCAR does not function as a CVB3 receptor (36). IgSF11-D2 has 31% homology, CD155-D2 has 21% homology, and CD80-D2 has no sequence similarities to hCAR-D2.…”
Section: Car-mediated Cvb3 Infection Does Not Require Glycosylation Omentioning
confidence: 99%
“…CAR is also a critical cell adhesion protein that plays a role in the junctional localization of important scaffolding proteins and cognate signaling proteins, such as PSD-95 and ASIC3 (Excoffon, Kolawole et al 2012). Moreover, the essential nature of CAR may be due to its ability to traffic or modulate the junctional stability of important proteins, such as MAGI-1, connexin 45, β-catenin, and ZO-1, particularly at cell junctions and the cardiac intercalated disc (Lim, Xiong et al 2008, Pazirandeh, Sultana et al 2011, Freiberg, Sauter et al 2014). MAGI-1 is an important scaffolding protein that can create a signalosome with over 20 distinct proteins that are involved in diverse cellular pathways, from adhesion to the regulation of signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on its endogenous cellular function have shown that CAR is a developmentally essential protein with important cardiac functions (Asher, Cerny et al 2005, Dorner, Wegmann et al 2005, Freiberg, Sauter et al 2014). In polarized epithelia, CAR is primarily a basolateral adhesion protein involved in the maintenance of cell-cell contacts (Walters, Freimuth et al 2002, Excoffon, Hruska-Hageman et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The coxsackievirus and adenovirus receptor (CAR) was identified as the cellular receptor for CVB3 [ 33 35 ]. Murine cardiac fibroblasts, cardiomyocytes, and macrophages were tested for the gene expression of CAR.…”
Section: Discussionmentioning
confidence: 99%